Pelvic pain correlates with peritoneal macrophage abundance not endometriosis. Issue 1 (March 2021) - Gibson, Douglas A; Collins, Frances; De Leo, Bianca; Horne, Andrew W; Saunders, Philippa T K
Abstract : Endometriosis is a chronic neuroinflammatory pain condition affecting 180 million women worldwide. Surgical removal or hormonal suppression of endometriosis lesions only relieves pain symptoms in some women and symptomatic relapse following treatment is common. Identifying factors that contribute to pain is key to developing new therapies. We collected peritoneal fluid samples and clinical data from a cohort of women receiving diagnostic laparoscopy for suspected endometriosis ( n = 52). Peritoneal fluid immune cells were analysed by flow cytometry and data compared with pain scores determined using the pain domain of the Endometriosis Health Profile Questionnaire (EHP-30) in order to investigate the association between peritoneal immune cells and pain symptoms. Pain scores were not different between women with or without endometriosis, nor did they differ according to disease stage; consistent with a poor association between disease presentation and pain symptoms. However, linear regression and correlation analysis demonstrated that peritoneal macrophage abundance correlated with the severity of pelvic pain. CD14 high peritoneal macrophages negatively correlated with pain scores whereas CD14 low peritoneal macrophages were positively correlated, independent of diagnostic outcome at laparoscopy. Stratification by pain subtype, rather than endometriosis diagnosis, resulted in the most robust correlation between pain and macrophage adundance. Pain score strongly correlated with CD14 high ( P = 0.007) and CD14 low ( P = 0.008) macrophages in patients with non-menstrual pain and also in patients who reported dysmennorhea (CD14 high P = 0.021, CD14 low P = 0.019) or dysparunia (CD14 high P = 0.027, CD14 low P = 0.031). These results provide new insight into the association between peritoneal macrophages and pelvic pain which may aid the identification of future therapeutic targets. Lay summary: Endometriosis is a common condition where cells similar to those that line the womb are found elsewhere in the body. It is associated with inflammation and pain in the pelvis and affects 180 million women worldwide. Current treatments are not effective for all patients and we, therefore, need to understand what causes pain in order to develop new treatments. We investigated the types of immune cells present within the pelvis of women undergoing investigation for suspected endometriosis. Disease diagnosis and stage (I–IV) was recorded along with pain score determined by questionnaire. We characterised the immune cells present and compared them to disease stage and pain score. We found that pelvic pain was linked to the abundance of immune cells but, surprisingly, not to disease stage. These findings suggest that immune cells are closely associated with pain severity in endometriosis and may be good targets for future endometriosis treatments.